2018
DOI: 10.3390/su10124339
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Connections between Agroecological Practices and Ecosystem Services: A Systematic Literature Review

Abstract: Current patterns of global change are threatening the supply of agrarian ecosystem services on which human well-being depends. Within this context, agroecology has emerged within political and scientific arenas as a socially equitable and ecologically sustainable alternative to conventional agriculture. We performed a systematic literature review to explore how agroecology and the ecosystem services framework have been adopted together in the scientific literature, focusing on studies including empirical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 63 publications
1
26
0
2
Order By: Relevance
“…According to Palomo-Campesino et al [34], agroecosystems reflects interactions between society and nature, however, inappropriate management can have negative consequences for the agrosystem. The content of available phosphorus in the soil changed more significantly.…”
Section: Resultsmentioning
confidence: 99%
“…According to Palomo-Campesino et al [34], agroecosystems reflects interactions between society and nature, however, inappropriate management can have negative consequences for the agrosystem. The content of available phosphorus in the soil changed more significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Crop diversification faces a typical situation of socio-technical lock-in of dominant food regimes [16]. It could be a pillar of agroecological transition, as it potentially has multiple sustainability benefits, such as reduced yield gaps and dependency on external inputs, increased biodiversity, limited economic risks, more varied landscapes, and enhanced provision of diverse ecosystem services [16,32,34]. Despite such well-known benefits, various studies have shown the adoption of diversification practices to be limited by barriers at all levels of food systems.…”
Section: Contrasting Food System Innovation Settings For Crop Diversimentioning
confidence: 99%
“…At last, studies showed that habitat heterogeneity affects the level of biodiversity in agricultural landscapes [1,7,102,103]. Both abandonment and intensification of Satoyama elements cause biodiversity loss.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…It has long been criticized as the major driving force of biodiversity loss [1][2][3]. However, recent research showed that traditional agricultural landscapes can maintain rich biodiversity and provide a bundle of ecosystem services [4][5][6][7]. Generally, the traditional agricultural landscape commonly encompasses the multiple uses of natural, semi-natural, and artificial ecosystems [8], where crop cultivated plots and adjacent vegetation and habitats are often integrated into a well-managed mosaic-like production landscape [9].…”
Section: Introductionmentioning
confidence: 99%